The Motif of Spiritual Awakening and its Implementation at the Chronotope Level in A.P. Chekhov's Short Story "The Student" - Mkrtchyan, Marianna (Bulletin of Yerevan University H: Russian Philology, 2026)
This article analyzes the motif of spiritual awakening in A.P. Chekhov's Easter story “The Student” (1894) within the context of the Gospel event of Peter's denial and its interpretation, which goes beyond its traditional meaning from the point of view of dogmatic theology and coinciding with it moral and philosophical interpretations of this Gospel event. In interpreting the work, we rely on an approach to the literary text as an open structure that allows for it to be read beyond the author's intention, but closely linked to it. In Chekhov's inclusion of the Gospel text in his work we see an intersection of various semantic codes that allow for dissimilar interpretations. Specifically, the Peter’s denial is viewed by us not only as a temporary apostasy and the manifestation of human weakness, but also as a consequence of an altered state of his consciousness. In the Gospel, it is reflected as sleep, which the disciples of Christ are not able to resist. Through that, deepens the theme of awakening in the story. In the story, we examine the problem of the human soul, searching for meaning in life and finding it through the experience of the Gospel events. In our analysis we rely on the features of the spatial and temporal organization of the text, in which we identify several forms of literary time (biographical, daily, calendar, cosmic), on the basis of which a picture of the hero's transition from a linear (horizontal) path to a spiritual vertical level is constructed.
Keywords: A.P. Chekhov; Easter story; “The Student”; Gospel; Peter's denial; Space; Time; Chronotope